CIC-rearranged Sarcomas: A Study of 20 Cases and Comparisons With Ewing Sarcomas. (March 2016) - Yoshida, Akihiko; Goto, Keisuke; Kodaira, Makoto; Kobayashi, Eisuke; Kawamoto, Hiroshi; Mori, Taisuke; Yoshimoto, Seiichi; Endo, Otone; Kodama, Narihito; Kushima, Ryoji; Hiraoka, Nobuyoshi; Motoi, Toru; et al.
Abstract : The CIC gene rearrangement exists in a subset of small round cell sarcomas. As the nosologic relationship of these sarcomas to Ewing sarcomas remains undetermined, we examined 20 CIC -rearranged sarcomas to compare their clinicopathologic features with those of Ewing sarcomas. The CIC -rearranged sarcomas were from a group of 14 men and 6 women with a median age of 24.5 years. The primary tumor sites included the limbs, trunk wall, internal trunk, lung, cerebrum, and pharynx. A comparison of the demographic and clinical characteristics of the 20 patients with CIC -rearranged sarcomas with those of the 53 near-consecutive patients with EWSR1 -rarranged Ewing sarcomas showed that there were no differences with respect to their ages and sexes. Although none of the CIC -rearranged sarcomas arose in the bone, 40% of the Ewing sarcomas primarily affected the skeleton. The overall survival of patients with Ewing sarcomas was significantly better than that for patients with CIC -rearranged sarcomas. A histologic comparison of the CIC -rearranged sarcomas with 20 EWSR1 -rearranged Ewing sarcomas showed significantly higher degrees of lobulation, nuclear pleomorphism, the prominence of the nucleoli, spindle cell elements, and myxoid changes in the CIC -rearranged sarcomas. Distinguishing immunohistochemical features included heterogenous CD99 reactivity, nuclear WT1 expression, and calretinin expression in the CIC -rearranged sarcomas and NKX2.2 expression in the Ewing sarcomas. CIC -rearranged sarcomas are distinct from Ewing sarcomas clinically, morphologically, and immunohistochemically, and they should be considered a separate entity rather than being grouped within the same family of tumors. Abstract : Supplemental Digital Content is available in the text.